Reading Pliny's Panegyricus Within the Context of Late Antiquity and the Early Modern Period - Dominik, William J. (2021)
One approach to the reading of Pliny’s Panegyricus is to examine later iterations and discussions of panegyric in Late Antiquity and the Early Modern Period for loci and passages that recall and discuss this earliest extant imperial panegyric. Although a surface reading of imperial panegyric, whether it is in the judicial or political context, is indisputably laudatory, the ambiguous undertones of a text like the Panegyricus will always be the subject of contestation among critics. Inevitably scholars who read imperial panegyric literally will not like an interpretation that opens up possibilities for a multivalent reading of Pliny’s panegyric on Trajan. The Panegyricus can be read firstly and most obviously as praise and flattery, even if such a reading includes the potential for the instability or slippage of flattery. But the hybrid nature of the genre it represents suggests that the Panegyricus can also be read in at least four other ways: as ceremony and celebration; as authorial self-positioning, self-fashioning, and self-representation; as exhortation, admonition, and advice, that is, as protreptic and didactic; and as potential admonishment and criticism. As later panegyric evidently was multi-dimensional and allowed for ambiguity and even criticism, it seems natural that the Panegyricus, which sometimes served as a model for the composition of subsequent panegyrics, would possess a similar capacity to function on a number of levels. The reception of Pliny’s Panegyricus by writers of Late Antiquity and the Early Modern Period not only provides evidence of its important role in the history of the genre of panegyric, but it also serves to illustrate the potential functions of the Panegyricus’ own narrative. The modern criticism levelled against the Panegyricus is largely attributable to its effusive flattery of the emperor, but the focus on this feature of the work has partly blinded readers to its more nuanced aspects. An examination of Pliny’s narrative techniques in the Panegyricus and its reception (and that of Graeco-Roman panegyric generally) during Late Antiquity and the Early Modern Period demonstrates that the oration had a number of potential functions that transcend the mere purpose of praising the emperor.